PELATIHAN AKUNTANSI TRANSAKSI PEMBELIAN MENGGUNAKAN PROGRAM ACCURATE BAGI SISWA/I SMA K1, JAKARTA - Hidajat, Nastasya Cindy; Yang, Amanda; Aileen; Sanjaya, Ivan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Trading companies are one type of business that dominates throughout the world. The most important thing in a goods company is the procurement of goods because this is the main resource so that the expected trading activities can be carried out. This Community Service Activity (PKM) is one manifestation of the Tri Dharma of Higher Education, to provide benefits to the community. The students have never studied purchasing transactions in accounting using the accounting program. It is hoped that this activity will provide benefits for Kristoforus 1 High School students to better understand the use of accounting programs in inputting company transactions, especially purchasing transactions. This training will focus on purchasing transactions. This activity will be carried out for 90 minutes in two offline sessions in October 2023. The activity includes presentation of material by the Untar PKM Team, then continued with practice questions and ending with a question and answer session. From the results of the questionnaire, it can be seen that the material presented was successfully accepted by the students and increased their knowledge.